Analysis of Aerostreet x Khong Guan Co-Branding Strategy as a Step of Innovation and Increase Customer Engagement - Artagnan, Frans Ruffino; Alam, Yunan Miftahul (IJESPG (International Journal of Engineering, Economic, Social Politic and Government), 2023)
This research uses descriptive qualitative methods that aim to explain factually through in-depth data collection. Data collection was conducted through interviews with key informants from Aerostreet as well as a review of relevant literature. The results showed that the co-branding strategy between Aerostreet and Khong Guan has succeeded in creating innovations that attract customers' attention. By combining a popular shoe brand with a well-known food brand, both can leverage each other's advantages to create greater added value. In addition, this co-branding has also succeeded in increasing customer engagement. Through this cooperation, Aerostreet and Khong Guan can attract the attention of different customers and expand their market share.